Designing Culturally Responsive Language Curricula - Muhammadiah, Mas’ud; Chai, Nong; Pao, Chai (Journal International of Lingua and Technology, 2024)
Language curricula often fail to address the diverse cultural backgrounds of learners, which can impact engagement and the effectiveness of language acquisition. In multicultural learning environments, culturally responsive curricula are essential to creating inclusive education that respects and integrates learners’ unique cultural experiences. This research aims to explore the design and implementation of culturally responsive language curricula that enhance learner engagement and improve language proficiency by aligning educational content with students’ cultural contexts. A qualitative research approach was employed, involving case studies of five educational institutions with diverse student populations. Data were collected through interviews with educators, curriculum developers, and students, as well as through analysis of existing curricula. The study examined how culturally relevant content and teaching methods were incorporated into language courses and evaluated their impact on student motivation, participation, and proficiency. The analysis also identified key strategies for designing culturally responsive curricula. The results indicated that integrating learners’ cultural backgrounds into the curriculum significantly improved engagement and language proficiency. Educators reported higher levels of student participation and motivation when the content reflected learners’ cultural identities and real-life experiences. Additionally, students showed greater retention of language skills when cultural relevance was emphasized in the learning process.